2017
DOI: 10.1016/j.conctc.2017.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of early use of AbobotulinumtoxinA after stroke on spasticity progression: Protocol for a randomised controlled pilot study in adult subjects with moderate to severe upper limb spasticity (ONTIME pilot)

Abstract: IntroductionApproximately 15 million people suffer a stroke annually, up to 40% of which may develop spasticity, which can result in impaired limb function, pain and associated involuntary movements affecting motor control.Robust clinical data on spasticity progression, associated symptoms development and functional impairment is scarce. Additionally, maximal duration of muscle tone reduction following botulinum toxin type A (BoNT-A) injections remains undetermined. The ONTIME pilot study aims to explore these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Full details of the ONTIME study (NCT02321436) protocol have been published [ 35 ]. ONTIME was conducted in accordance with the Declaration of Helsinki, International Conference on Harmonisation Good Clinical Practice Guidelines, and local regulatory requirements, with approval from relevant independent ethics committee/institutional review boards.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Full details of the ONTIME study (NCT02321436) protocol have been published [ 35 ]. ONTIME was conducted in accordance with the Declaration of Helsinki, International Conference on Harmonisation Good Clinical Practice Guidelines, and local regulatory requirements, with approval from relevant independent ethics committee/institutional review boards.…”
Section: Methodsmentioning
confidence: 99%
“…Doses were administered per muscle according to investigators’ judgements. Recommended dosing regimens were previously published [ 35 ]. Most patients participated in occupational and physiotherapy practices.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Treatment with BoNT-A is often deferred until the patient shows clinical signs of spasticity, usually at least 3 months post-stroke [13]. However, recent studies have demonstrated that treatment with BoNT-A as early as 2-12 weeks following stroke may prevent the development of spasticity and improve muscle tone, thus improving prognosis [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%